Factors associated with early initiation of disease-modifying drug treatment in newly-diagnosed patients with multiple sclerosis. (3rd August 2018) - Edwards, Natalie C.; Munsell, Michael; Menzin, Joseph; Phillips, Amy L.
Abstract: Objective: To examine the time to first disease-modifying drug (DMD) treatment and to identify factors associated with early DMD initiation in newly-diagnosed patients with MS. Methods: This retrospective cohort study included newly-diagnosed patients with MS from a US administrative claims database, aged 18–65 years, with a first MS diagnosis (ICD-9-CM code: 340.xx) between January 1, 2007 and June 30, 2013 (index date), continuous eligibility for 12 months pre- and 24 months post-index, and initiated DMD treatment within 2 years. Time to first DMD within 24 months post-index was evaluated. A logistic regression model predicted earlier initiation of DMD treatment (within 60 days of MS diagnosis). Results: In total, 37.4% of patients initiated DMD treatment within 2 years of MS diagnosis and were included in the primary analysis ( n  = 7, 124). Mean (standard deviation [SD]) time from MS diagnosis to first DMD was 112.6 (148.3) days (median = 51); 30.7% received first DMD in <30 days, 55.1% in <60 days, and 18.5% not until ≥180 days after diagnosis. Logistic regression found that younger age; not living in the Northeast; diagnoses of balance disorders, numbness, and optical neuritis; the absence of musculoskeletal diagnoses; and a neurologist visit or MRI within 90 days before diagnosis were associated with DMD initiation within 60 days. Conclusions: In this population of patients initiating DMD treatment within 2 years of MS diagnosis, mean time to first DMD was 112.6 days. Identifying factors associated with delayed treatment may provide better understanding of the reasons for delay, leading to improved disease management.